Laparoscopic repair of recurrent congenital diaphragmatic hernia: A case report - Anjola Onifade; Dimitrios Antoniou; Alexandra Robotin-Pal; Saravanakumar Paramalingam (Elsevier, 2023)
Introduction: Recurrent herniation is a well-recognised complication following the repair of a congenital diaphragmatic hernia (CDH). There is no consensus on the optimal surgical approach to manage recurrent CDH. We present a case of laparoscopic correction of recurrent herniation using a non-absorbable patch. Case Presentation: A 13-month old girl presented to the outpatients department with constipation and breath-holding attacks, previously having undergone left CDH surgery on the 7th day of life. The original operation was performed via a subcostal incision and a primary repair was carried out with interrupted non-absorbable sutures. Chest X-ray demonstrated elevation of the left hemi diaphragm with a posterior 'bulge' suggesting a recurrence. An elective diagnostic laparoscopy was performed confirming the recurrence with transverse colon herniation through a left postero-lateral diaphragmatic defect size 5 × 5 cm and complete absence of the previously noted posterior rim. There were significant adhesions to the anterior abdominal wall, including the spleen, which were divided and mobilised haemostatically to allow complete assessment of the defect. A patch repair was performed using synthetic mesh anchored with interrupted non-absorbable sutures. Total operating time was under 120 minutes. The patient was discharged on the 3rd post-operative day with minimal analgesic requirements and no evidence of recurrence on follow-up radiographs. Conclusion: Laparoscopic repair is a safe and effective option for cases of CDH recurrence and is technically feasible despite the operative challenges that the surgeon will inevitably face as demonstrated in this case.